QUALITY OF INJURED TEETH HYGIENE INDEX AS A NEW APPROACH TO ASSESSING THE QUALITY OF HYGIENIC CARE - Chehertma, E.I.; Bidenko, N.V.; Savychuk, O.V.; Chalyy, K.O. (World of Medicine and Biology, 2024)
The study focuses on evaluating oral hygiene care for injured teeth in children, with the development of the Quality of Injured Teeth Hygiene index. The research targeted children aged 8 to 12, whose teeth, due to traumatic injuries, were immobilized with wire-composite splints. The Quality of Injured Teeth Hygiene, Silness-Loe, and Sulcus Bleeding indices were used to compare the quality of care for injured and healthy teeth to determine the most informative approach. The results demonstrated that the Quality of Injured Teeth Hygiene index showed a stronger correlation with the Sulcus Bleeding indicator, indicating its sensitivity to local inflammatory changes in injured areas. It was found that the use of Quality of Injured Teeth Hygiene index allows dentists to monitor oral hygiene status and adjust recommendations to improve care for injured teeth, thus enhancing treatment effectiveness and reducing the risk of infectious complications.
Keywords: children; biofilm; oral hygiene; trauma; traumatic dental injuries; splinting of teeth; tooth damage